Montessori Methods for Supporting Neurodiverse Children - Koifman, Julia (Language, Literature and Education: Research Updates Vol. 4, 2025)
Montessori schools place a high value on respecting others, embracing diversity, and promoting inclusivity. Children who have disabilities or neurodivergent conditions tend to thrive socially in Montessori environments, where they are warmly welcomed into a multi-age peer group that emphasises compassion and acceptance. Montessori principles play an important role in children's lives. This principle is a guide that recognises and adjusts to each child's developmental level and interests to provide personalised instruction, which is crucial for neurodiverse students. As a result, children can progress through the curriculum at their own pace without the pressure of meeting predetermined grade-level benchmarks while being challenged in all areas of learning at the appropriate level. Multi-sensory activities and hands-on learning facilitate learning in the Montessori classroom, as well as differentiated teaching and individual approach, depending on each student's needs. Students are encouraged to learn by doing and have the freedom to move around, which benefits those who require physical activity or may have difficulty paying attention in traditional classroom settings. In addition, Montessori classrooms provide a structured environment that assists children in developing organisational and time management skills, ultimately leading to greater independence. The system also values each neurodivergent and neurotypical child's unique learning path and tailors their educational plan to match their individual developmental level, learning style, and interests. So, each child can receive customised instruction and advance through the curriculum at their own speed. Access to different devices that facilitate communication and specialised equipment that helps with sitting, writing, reading, or moving is crucial in special needs classrooms or homes. These items are necessary tools for supporting individuals in such settings. The Montessori curriculum is designed based on certain principles derived from the philosophies about how children learn and think, and this approach is particularly beneficial for students with learning difficulties and those with cognitive and developmental disorders. In conclusion, by embedding universal support and creating multiple access routes to learning, it can be ensured that all students have the opportunity to work diligently and achieve success in classrooms and beyond. This requires trust and openness to co-create an inclusive learning environment that enables all students to thrive.